2016
DOI: 10.1016/j.stem.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Multipotency of Adult Hippocampal NSCs In Vivo Is Restricted by Drosha/NFIB

Abstract: SUMMARYMulti-lineage neuronal, astrocytic and oligodendrocytic potential is considered a neural stem cell (NSC) trait. However, hippocampal NSCs generate neurons and astrocytes but not oligodendrocytes in vivo and how this is regulated is unknown. Here we show that the RNAseIII Drosha is an intrinsic regulator of stem cell maintenance and differentiation in the adult mouse hippocampus. Inactivation of Drosha results in exhaustion of the NSC pool, premature arrest of neurogenesis, and induction of oligodendrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(133 citation statements)
references
References 46 publications
(61 reference statements)
2
130
0
1
Order By: Relevance
“…The NFI family has been extensively described in the developing brain, and have been implicated in multiple neurodevelopmental disorders (Malan et al, 2010), but how these factors function in the adult hippocampus is unclear. A recent study revealed a role for NFIB in promoting oligodendrogenesis within the adult SGZ (Rolando et al, 2016). Here, we present a contrasting role for NFIX within the adult hippocampus, revealing that NFIX drives a program of neuroblast differentiation and suppresses the latent potency of hippocampal precursor cells to generate…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…The NFI family has been extensively described in the developing brain, and have been implicated in multiple neurodevelopmental disorders (Malan et al, 2010), but how these factors function in the adult hippocampus is unclear. A recent study revealed a role for NFIB in promoting oligodendrogenesis within the adult SGZ (Rolando et al, 2016). Here, we present a contrasting role for NFIX within the adult hippocampus, revealing that NFIX drives a program of neuroblast differentiation and suppresses the latent potency of hippocampal precursor cells to generate…”
Section: Discussionmentioning
confidence: 69%
“…NFIX, and other NFIs are wellestablished regulators of astrocyte (Barry et al, 2008;Kang et al, 2012;Heng et al, 2014) and oligodendrocyte differentiation (Wong et al, 2007;Zhou et al, 2015;Rolando et al, 2016). Under physiological conditions, AH-NSCs generate astrocytes in addition to neurons (Bonaguidi et al, 2011).…”
Section: Deletion Of Nfix From Hippocampal Progenitors Leads To the Amentioning
confidence: 99%
See 3 more Smart Citations